Efektifitas Autoplay dalam Meningkatkan Hafalan Kosakata pada Siswa MTs At Taqwa Harapan Baru Samarinda - Mustamin Mustamin; Nur Hasanah; Syarifaturrahmatullah Syarifaturrahmatullah (Borneo Journal of Primary Education, 2022)
The The background of this research is the process of learning Arabic in Mts At Taqwa Harapan Baru which is still traditional and frequent rule out the use of instructional media, even though schools have the facilities are fairly complete. This is due to a lack teacher's ability to be creative and innovate to design media learning to be applied in the learning process in the classroom, so impact on the enthusiasm and focus of student learning. The purpose of this study was to determine the effectiveness of autoplay in increasing vocabulary memorization in Mts At Taqwa Harapan Baru Samarinda students. The research method used is a type of quantitative research The research results obtained as follows: response results teachers on autoplay media studio media obtained a percentage of 81.04%. very good category, while the results of student responses to autoplay media This research is expected to contribute in the form of media learning in order to assist the teacher in conveying the material learning and also helps students to more easily accept and master the Arabic language. In addition, this research is also expected able to motivate teachers to create learning media that innovative, and also to increase students' interest and motivation to learn Arabic.